Case Report: Early Treatment With Chenodeoxycholic Acid in Cerebrotendinous Xanthomatosis Presenting as Neonatal Cholestasis - Degrassi, Irene; Amoruso, Chiara; Giordano, Giuseppe; Del Puppo, Marina; Mignarri, Andrea; Dotti, Maria Teresa; Naturale, Mauro; Nebbia, Gabriella (Frontiers in Pediatrics, 2020)
Background: Cerebrotendinous xanthomatosis (CTX) is an inborn disorder of bile acid synthesis which causes progressive accumulation of toxic metabolites in various organs, particularly in brain and tendons. Most cases are diagnosed and treated in the second or third decade of life, when neurological involvement appears. We describe a case of CTX presenting as neonatal cholestasis. Results: The child presented cholestasis at two months of life. In the following months jaundice slowly disappeared, with a normalization of bilirubin and aminotransferases respectively at 6 and 8 months. A LC-Mass Spectrometry of the urines showed the presence of cholestanepentols glucuronide, which led to the suspicion of cerebrotendinous xanthomatosis. The diagnosis was confirmed by the dosage of cholestanol in serum and the molecular genetic analysis of the CYP27A1 gene. Therapy with chenodeoxycholic acid (CDCA) was started at 8 months and is still ongoing. The child was monitored for thirteen years by dosage of serum cholestanol and urinary cholestanepentols. A strictly biochemical and neurological follow up was performed and no sign of neurological impairment was observed. Conclusions: Prompt diagnosis and treatment of CTX presenting as neonatal cholestasis may prevent further neurological impairment.